Urgensi Mengembangkan Literasi Informasi dan Literasi Budaya Pada Anak Usia Dini - Purwanto Putra; Renti Oktaria (Universitas Lampung, 2020)
This study discusses the urgency of developing Information Literacy and Cultural Literacy in Early Childhood in the context of the application of the National Literacy Movement. The purpose of this paper is to photograph the concept and the extent of the urgency of the introduction of information literacy skills and cultural literacy in early childhood in supporting the application of the National Literacy Movement. Review the role and internalization of daily activities and teaching and learning activities in the classroom in the context of information literacy and cultural literacy. This research uses a qualitative research approach with literature study design and conceptual analysis. The results of this study indicate that there is a need for early childhood recognition and planting in relation to the ability of information literacy and cultural literacy in responding to the development of global society and multiculturalism. From this study it was also revealed that there was a need and attention from stakeholders to facilitate and reduce the concept of information literacy and cultural literacy for young children in a more complete grand design and technical implementation in the community and schools.Keywords: information literacy, cultural literacy, early childhood, early childhood Education. DOI: http://dx.doi.org/10.23960/jiip.v2i2.21818